Physical mechanisms and models of long-term transformations of radiative recombination in n-GaAs due to the magnetic field treatments - Milenin, G.V.; Red’ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Simulation of long-time changes in photoluminescence of n-GaAs has been performed, and the mechanism of transformation of the defect structure caused by magnetic field treatments has been represented.